2008
DOI: 10.1093/aob/mcn141
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Maize Root-tip Elongation by Salt and Osmotic Stress do not Correlate with Apoplastic O2•− Levels

Abstract: The lack of association between apoplastic O(2)(*-) levels and root growth inhibition under hyper-osmotic stress leads us to hypothesize that under those conditions the role of apoplastic O(2)(*-) may be to participate in signalling processes, that convey information on the nature of the substrate that the growing root is exploring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
3
19
0
1
Order By: Relevance
“…Root tips of P. coloratum plants grown under alkaline conditions showed increased superoxide production (Figure a). The plasma membrane‐bound superoxide‐generating NADPH oxidase complex is mainly responsible for apoplastic superoxide production in roots (Bustos et al ., ). This complex is a key player in the ROS signalling network that participates in growth and development regulation as well as in the responses to multiple stress conditions (Suzuki et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Root tips of P. coloratum plants grown under alkaline conditions showed increased superoxide production (Figure a). The plasma membrane‐bound superoxide‐generating NADPH oxidase complex is mainly responsible for apoplastic superoxide production in roots (Bustos et al ., ). This complex is a key player in the ROS signalling network that participates in growth and development regulation as well as in the responses to multiple stress conditions (Suzuki et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Superoxide presence in root tips was determined with nitro blue tetrazolium (NBT), following Bustos et al . (). Oxidative damage in leaves was evaluated by malondialdehyde (MDA) concentration, measured in alcohol extracts according to Heath and Parker ().…”
Section: Methodsmentioning
confidence: 97%
“…For example, growth rates may be generally decreased, maximum growth rates may be reduced or shifted proximally, and the elongation zone may be shortened (Fricke, 2002;Rodríguez et al, 2004). Reductions in growth rates are normally observed in the decelerating zone of growth rates, but rates in the growth accelerating zone, closest to the meristem, may remain unaltered (Ortega et al, 2006), as observed in roots under water stress (Sharp et al, 1988;Fan and Neumann, 2004) or salinity (Bustos et al, 2008).…”
Section: Elongation Growth In the Ezmentioning
confidence: 99%
“…Treatments with inhibitors of polyamine oxidase, a salt-tolerant enzyme, suggest that this enzyme may also play a role in maintaining leaf growth under salinity (Maiale et al, 2008). Nevertheless, in maize root tips, detailed studies have indicated that the distribution of accelerating growth and highest d O 2 À levels coincide along the root tip in non-stressed plants, while growth changes due to stress and the distribution of apoplastic d O 2 À are not associated (Bustos et al, 2008).…”
Section: Ros and The Regulation Of Leaf Growth Under Stressmentioning
confidence: 99%
See 1 more Smart Citation